EFFECT OF DIETARY OREGANO Origanum vulgare ESSENTIAL OIL CONTAINED WITH CARVACROL AND THYMOL ON THE GROWTH PERFORMANCE AND RESISTANCE OF STRIPED CATFISH Pangasionodon hypophthalmus AGAINST Aeromonas hydrophila INFECTION - Novriadi, Romi; Farkan, Mochammad; Sabaruddin, Muhammad; Panjaitan, Amyda; Nurraditya, Lakonardi; Santika, Ayi; Permana, Luki Sanjaya Setia; Karakatsouli, Nafsika; Nitsas, Fotios (Agency for Marine and Fisheries Extension and Human Resources, 2024)
The production efficiency of striped catfish Pangasianodon hypophthalmus is very dependent on the quality of feed, which can increase the fish’s growth rate and health condition. Thus, the aimed of this study was to investigate the effects of different levels of Oregano Essential Oil (OEO) contained with thymol and carvacrol, at the concentration level of 0.1, 0.2, and 0.4% OEO, which is applied using top-dressing method and included in feed formulation on the growth rate, body composition, digestive health and resistance of striped catfish P. hypophthalmus against the pathogenic bacteria Aeromonas hydrophila. The results of growth trials using top-dressing method for 122 days using formulated feed method for 70 days showed that the application of OEO yielded better growth than the control, with 0.2% OEO providing better growth performance than 0.1 and 0.4% OEO. The body composition analysis results also showed a better level of nutrient absorption in fish fed the OEO-based diet compared to the control. For the number of bacteria in the digestive tract, OEO supplementation can also significantly reduce the number of bacteria compared to fish-fed control feed. The challenge test results after the fish were given treatment feed for 24 days showed that the application of 0.1% OEO provided better protection against Aeromonas hydrophila. However, there was no significant difference with 0.2% OEO. The application of 0.2% OEO can be recommended to increase the efficiency and productivity of catfish cultivation.